Ecumenical Community : Language and Politics of the Ummah in the Qurʾan - Zafer, Hamza, (Texts and Studies on the Qurʾān ;, 2021)
"In Ecumenical Community, Hamza M. Zafer explores the language and politics of community-formation in the Qurʾan. Zafer proposes that ecumenism, or the inclusivity of social difference, was a key alliance-building strategy in the western Arabian proto-Muslim communitarian movement (1st/7th century). The Proto-Muslims imagined that their pietistic community-the ummah-transcended but did not efface prior social differences based in class, clan, and custom. In highlighting the inclusive orientation of the Qurʾan's ummah-building program, Zafer provides new insights into the development of early Islam and the period preceding the Arab conquests"--